Tax Incentives for Small and Medium Businesses in European Union Countries in the Crisis Period - Ordynskaya, Marina Evgenievna; Silina, Tatyana Aleksandrovna; Karpenko, Svetlana Viktorovna; Divina, Lala Eldarovna (International Journal of Economics and Financial Issues, 2016)
In the majority of world countries in all areas of economy small and medium businesses (SMB) account for a considerable share in the total amount of the gross domestic product, production of goods and provision of services. However, the main thing is that SMB allow to provide the population employment and stable development of the country as a whole. That is why today issues related to organizing an optimal system of SMB taxation for the purpose of contributing to the development and agreeing with the interests of the state, the society as a whole and entrepreneurs remain urgent. The article generalizes the global experience of tax regulation of small and medium businesses (SMB) development and defines the peculiarities of its taxation focused on long-term goals of economic development. As a result of the conducted research, the macroeconomic essence of the impact of taxation on the development and functioning of SMB was defined. Contemporary world tendencies of using mechanisms of taxation in the system of tax regulation of SMB were analyzed. Top-priority areas of using mechanisms of SMB taxation were defined and generalized taking into account peculiarities of economies of EU countries. Keywords: small business; small and medium business; economic development; tax regulation; tax incentives. JEL Classifications: H25, L25, M21